Provisions of the uncertain fate of the Penal Code - كاظم, كريم سلمان (Journal of Legal Sciences, 2019)
Under the provisions of the old penal laws were criminal responsibility collectively If someone commits murder of the tribe was the victim belongs to another tribe was wasting his blood as a murderer and have each person of the tribe personally responsible for this crime. If it does not contribute to it or did not know, however, committed to achieving voices calling goodness and justice demand soared to impose punishment on the person who is connected to the crim.The French Revolution and its leaders credited with establishing the principle of personal punishment and responsibility in contemporary penal laws did this concept is limited to the advancement of the criminal liability of play a role in the commission of the crime, but must that the person is punished to the extent that contributed to the commission of the Reus behavior But it must be punished to the extent the person committing the tastiest contributed Jerma.ovi behavior discussed this uncertainty that surrounds really certain of the acts have achieved the result rea which can not be with him to assign the crime to him, but hard each and every one of them has been released from an activityThe issuance of this activity is equally uncertain right of every one of them and so it must be eliminated punishment commensurate with the uncertainty which is less than the punishment that will be signed on the actor if he is known as if everyone was punished Baquba actor resolve injustice to the accused who their actions did not contribute to the crime, even escaped death everyone from the penalty to resolve injustice to society as a whole.